Observation of the Fe—CN and Fe—CO Vibrations in the Active Site of [NiFe] Hydrogenase by Nuclear Resonance Vibrational Spectroscopy - Kamali, Saeed (2012)
[Image: see text] Nuclear inelastic scattering of (57)Fe labeled [NiFe] hydrogenase is shown to give information on different states of the enzyme. It was thus possible to detect and assign Fe–CO and Fe–CN bending and stretching vibrations of the active site outside the spectral range of the Fe–S cluster normal modes.